A leitura literária de mulheres na EJA - Mariana Cavaca Alves do Valle (2010)
The research that led to this masters dissertation sought to understand the practices of literary reading among woman who were taking part in Youth and Adult Education Program (EJA). It was intended to describe and analyze both practices and strategies these people use to withstand perspectives that deny the presence of literary reading in their social environment, where this incident turns out to be considered unlikely to happen. Thus, through the investigation of seven cases, wesought to identify, aprehend and reconstruct the practices of literary reading by women taking part in Youth and Adult Education Program (EJA), taking into consideration the various factors that influence readers development. In order to develop this work, we tried to establish a relationship between three fields of study youth and adult education, literary readers development and gender which can provide us some elements for the reflection on a group of female readers that participate in Youth and Adult Education Programs (EJA), their specificities andaccessibility to cultural goods, specifically to literary texts. For this, we used the qualitative methodology as a research strategy. The data were collected from interviews involving the selected women. The found results originate from reports that show life trajectories marked by difficult access to written materials, especially in childhood. Among other findings, the analysis reveals the influence of employers as being the main mediators of reading among the women surveyed.